In-situ pore size investigations of loaded porous concrete with non-destructive methods. (September 2018) - Rifai, H.; Staude, A.; Meinel, D.; Illerhaus, B.; Bruno, G.
Abstract: Subject of this investigation is the in-situ evolution of pore volume and pore size distribution in Ytong (a porous concrete material) under increasing pressure with two different non-destructive analytical methods: Nuclear Magnetic Resonance (NMR) and X-ray Computed Tomography (CT). For both methods special strain devices to apply external pressure were constructed. The results from the two techniques yield complementary information on the pore size distribution and allows covering different pore size regions.